The Reproduction of Javanese Ethnic Identity among Migrant Javanese Communities through Janengan Art in Kebumen Village, Lampung - Nur Julian Majid; Chuna Kafia Dilla (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This article examines the role of Janengan performing art in reproducing Javanese ethnic identity among Javanese migrant communities in Kebumen Village, Lampung. Within a multiethnic social setting and migratory space, Janengan is understood not merely as an Islamic-Javanese religious expression but as a cultural practice that actively sustains ethnic continuity. The study addresses how Janengan functions as a medium for maintaining and renegotiating identity in a context marked by cultural interaction and social mobility. Employing a qualitative approach grounded in cultural ethnography and oral history, data were collected through participant observation, in-depth interviews, and literature review. The findings reveal that Janengan reproduces ethnic identity through the consistent use of the Javanese language, collective performance patterns, intergenerational transmission of religio-cultural values, and the reinterpretation of symbolic elements such as sajen. At the same time, it serves as a space for social solidarity and adaptive negotiation of Islamic-Javanese identity within a multiethnic environment. The article argues that Janengan operates as a dynamic cultural strategy through which Javanese migrants preserve and reconstruct their ethnic identity in migratory settings.